THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVING ACCOUNTABILITY PUBLIC SECTOR FINANCE: A THEORETICAL PERSPECTIVE - Nindya Sari; Novita Sri Anggraeni; Hotnida Sari Tanjung; Eka Nurmala Sari (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the role of information technology in improving public sector financial accountability in Indonesia. Thedevelopment of digital technology has encouraged the government to implement electronic-based financial information systems toincrease transparency, effectiveness, efficiency, and oversight of state and regional budget management. This study employed aqualitative method with a literature study approach through the collection of secondary data from scientific journals, books, officialgovernment documents, and academic articles for the 2021–2025 period. The analysis was conducted using thematic techniques.Analysis to identify key themes related to digital transparency, financial information systems, reporting automation, and the challengesof implementing information technology in the public sector. The results of the study indicate that the application of informationtechnology such as SIMDA, SIPKD, SPAN,e-budgeting,e-planning,e- procurement, Ande-reporting can improve the quality ofgovernment financial reports through faster, more accurate, relevant, and transparent data presentation. Furthermore, informationtechnology also strengthens internal and external oversight through digital audit trails and real-time access to information. However, the implementation of information technology still faces various obstacles such as limited human resources, uneven technologicalinfrastructure, resistance to organizational change, and data security risks. This research contributes to the development of digitaltransformation studies in public financial governance and provides recommendations for the government to increase humanresource capacity and invest in technological infrastructure to support better public sector financial accountability.